Prevalence and risk factors of the most common multimorbidity among Canadian adults - Obed Mortey; Gerald Mugford; Kris Aubrey-Bassler; Hensley H. Mariathas; Ugochukwu Odimba; Zhiwei Gao (PLoS ONE, 2025)
Background The number of persons living with multimorbidity–defined as the co-occurrence of at least two chronic conditions in the same individual–is growing globally, especially in developed countries. Traditionally, this increase has been attributed to a growing aging population, sedentary lifestyle, obesity, low socioeconomic status, and individual genetic susceptibility. Objective To investigate the prevalence and associated risk factors of the most common multimorbidity (MCM) among Canadian middle-aged and older adults. Method Relevant data on all 30,097 middle-aged and older Canadian adults (aged 45 to 85 years) from the Canadian Longitudinal Study on Aging were used for this study. To identify the specific sociodemographic risk factors associated with the MCM, we used survey-specific logistic regression. Findings Overall, co-occurrence of osteoarthritis and hypertension was identified as the MCM among Canadian adults aged 45+ with an estimated prevalence of 16.5%. The results from multivariate analysis showed that seven factors were significantly associated with increased odds of the MCM, which included increasing age, being retired from work (retired vs not retired), poorer rating of perceived health, (very good, good, poor vs excellent), increasing problems with sleep quality (satisfied, dissatisfied vs neutral), and abnormal body-mass index (underweight, overweight, obese vs normal). Also, residents in other urban centres had significantly lower odds than those in urban core. Persons living in Atlantic Canada, Ontario and Quebec were at increased odds of having the MCM compared to those in British Columbia. The odds of the MCM associated with increasing age was significantly higher among Females (OR = 1.12, 95% CI = 1.11–1.13) than Males (OR = 1.08, 95% CI = 1.07–1.10). Conclusion Multimorbidity is a common feature among Canadian adults. The identification of the most prevalent patterns and associated risk factors in this study provides fresh insights into the etiology, progression, and possible prevention of the MCM among Canadian adults.